Major hazards and disaster response capacity of Dadeldhura district - Pariyar, Raj Kumar; Neupane, Basanta Kumar (Geographical Journal of Nepal, 2020)
This study endeavours to explore the major hazards and the response capacity to disaster of Dadeldhura district. It used checklist to collect information on hazard ranking and capacity assessment. Similarly, key informant interview conducted with the key portfolios and members of district disaster management committee and Nepal Red Cross Society. Likewise, one focus group discussion was conducted with the purpose to draw insights of major disaster and capacity. Moreover, a district disaster preparedness plan was reviewed to understand the context of hazard and response. The major hazards of Dadeldhura district are landslide, flood, hailstone, fire, endemic, drought, thunderbolt and earthquake. Among all hazards landslide is in the first and flood is in the second rank based on damage and loss of physical property and livelihood. According to the district disaster preparedness and response plan, 2075, nine clusters have formed and updated emergency response plan for effective action in Dadeldhura. Among the nine clusters, this study only includes the search and rescue cluster to assess disaster response capacity. It has been found that out of nine clusters, search and rescue cluster seems progressive. However, the number of search and rescue trained people need to be increased. Likewise, the facility of ambulance and fire brigades need to extend in each rural municipality. Existing ambulance also need to be repaired and maintained regularly. The existing capacity is not enough to disaster response so, new efforts need to have been updated by DPRP with new activities to enhance the capacity.